Socialization and Assistance of MSME K3 Culture in Small and Medium Industries (IKM) in Malino, Gowa Regency - Irwan Setiawan Muthalib; Syamsul Bahri; Sapta Asmal; Kifayah Amar; Armin Darmawan; Maula Sidi Muhammad; Andry Yusdi (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2025)
This community service program (PkM) focuses on empowering small and medium industries (SMEs) producing tenteng in Malino, Gowa Regency, through socialization and mentoring activities aimed at increasing awareness of occupational health and safety (OHS) in the workplace and creating an environmentally friendly working environment. Small and medium industries serve as the driving force of the national economy, contributing significantly to employment and economic growth. However, many SME actors face challenges in implementing occupational safety and health standards due to limited resources and knowledge. This program aims to enhance the awareness and compliance of SME actors regarding occupational health and safety aspects. Through training, socialization, and the implementation of OHS standards, it is expected that the risks of accidents and occupational diseases can be minimized, productivity can be improved, and a safe and healthy work environment can be established. The methods used include providing education and assistance in hazard identification. The pre-test results showed participants’ understanding levels ranged from 8% to 21%, while the post-test results after the socialization showed a significant improvement, reaching 66% to 85%. These results indicate that the socialization and mentoring activities effectively improved participants knowledge and awareness of OHS culture, particularly regarding hazard identification, prevention measures, and the proper use of fire extinguishers.